Evaluation of carbon reduction through integration of vertical and horizontal landscape design for hotel premises - Othman, Rashidi; Abu Kasim, Siti Zubaidah; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim (Triveni Enterprises, 2016)
Hotel premises is a fundamental component of the tourism and hospitality. The design, construction, operation and end-of-life-cycle processes of hotel premises built the environment by which it exerts both positive and negative impacts on the guest and surrounding environment. Carbon emission from hotel premises are one of the major sources for greenhouse effect in urban areas. To counteract these tendencies, it is therefore necessary to identify green building practices that can be implemented over the hotel building's carbon emission in order to reduce its environmental impact as minimize the operational cost while maximizing economic and social opportunities. This study proved that through a substantial integration of spatial landscape design in combination with the right selection of plant materials based on its characteristics, carbon sequestration rate in a hotel premise can be optimized. Consequently, the role of these plants and trees in sequestering carbon emission will be best understood and the greatest opportunity as a carbon sink may be explored. This study aimed to predict carbon sequestration rate by plant materials through integration of vertical and horizontal landscape design. The decisive outcome of this study is a green practice applied in monitoring carbon toxicity and a cost effective environmental friendly carbon neutralization.